ROLE OF MULTI-PARTY SYSTEM IN THE NATIONAL INTEGRATION OF PAKISTAN - Sakeena (Journal of Peace, Development and Communication, 2024)
This study focuses on the Multi-party political system of Pakistan and its role and effects on the national integration in Pakistan. The researcher try to finds out the prospects and challenges of this political system in Pakistan. This study was carried out with the qualitative research methodology. First the background of the multiparty system of Pakistan was discussed and to find out the effects of this multiparty system on the national integration of Pakistan the primary data was collected through semi-structured interview from the political experts, scholars and political commentators through convenient sampling. Data was analyzed by the thematic analysis. During the analysis of data the researcher came across different positive and negative themes. But overall review which the researcher discovered from the analysis of the data was that multiparty system has a key role in the national integration of Pakistan, but the beneficial results are not seen in our society because there are many basic issues in our political system.